Pengaruh Perputaran Modal Kerja, Perputaran Piutang, Perputaran Persediaan, Perputaran Kas Terhadap Profitabilitas Perusahaan Manufaktur Subsektor Makanan Dan Minuman Periode Tahun 2018-2021 - Aniqotunnafiah Aniqotunnafiah; Heru Yulianto; Utami Puji Lestari (Journal Of Business, Finance, and Economics (JBFE), 2023)
This study aims to analyze the effect of working capital turnover, accounts receivable turnover, inventory turnover and cash turnover on profitability in food and beverage companies listed on the Indonesia Stock Exchange for the period 2018-2021. The population in the study are food and beverage companies listed on the Stock Exchange Indonesia. The samples that meet the criteria based on the purposive sampling method in this study are 48 manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The analysis used is multiple regression analysis which serves to see the effect of independent variables on the dependent variable both jointly and individually which is preceded by the classic assumption test which consists of a normality test, multicollinearity test, autocorrelation test and heteroscedasticity test. While hypothesis testing is done using the t test. The results of data analysis show that working capital turnover has an effect on profitability, accounts receivable turnover has no effect on profitability, inventory turnover has an effect on profitability, cash turnover has no effect on profitability.